(untitled) (Swiss Medical Weekly, 2025)
AIMS: Heterogeneous results regarding changes in the risk of preterm births and other perinatal outcomes during COVID-19-related restrictions (lockdowns) have been reported. We aimed to investigate the association between adverse birth outcomes and the initial COVID-19-related lockdown in Switzerland in 2020. AIMS: Heterogeneous results regarding changes in the risk of preterm births and other perinatal outcomes during COVID-19-related restrictions (lockdowns) have been reported. We aimed to investigate the association between adverse birth outcomes and the initial COVID-19-related lockdown in Switzerland in 2020. METHODS: We included singleton births recorded in the nationwide statistics of outpatient midwifery services in Switzerland (2018–2020). Using logistic regression, we estimated odds ratios (ORs) with 95% confidence intervals (CIs) for the risk of three birth outcomes between 16 March 2020 and 10 May 2020 (lockdown period) compared to any time between January 2018 and the start of the lockdown period. The outcomes of interest were preterm birth (<37 weeks), caesarean section and an Apgar score <7 at 5 minutes of age. Analyses were adjusted for calendar day and month and for geographical region. We conducted sensitivity analyses by geographic region. RESULTS: Of 218,273 singleton births between January 2018 and December 2020, 5.3% were preterm births, 30.2% were caesarean sections and 2.2% resulted in a newborn with an Apgar score <7 at 5 minutes. The risk of preterm birth was slightly but not statistically significantly higher during the lockdown period in Switzerland (OR: 1.09, 95% CI: 0.97–1.22). This was driven by an OR for preterm birth of 2.05 (95% CI: 1.10–3.85) for the canton of Ticino, which accounted for most COVID-19 infections during this time, but with no meaningful change in risk of preterm birth in other regions of Switzerland. We did not observe any change in the proportion of caesarean sections during the lockdown period. The Switzerland-wide risk of a recorded Apgar score <7 at 5 minutes had an OR of 1.41 (95% CI: 1.19–1.69), again driven by the highest OR of 4.60 (95% CI: 1.70–12.34) in the canton of Ticino as well as increased ORs in Geneva (2.40, 95% CI: 1.20–4.70) and Bern (2.84, 95% CI: 1.79–4.48). CONCLUSIONS: The risk of birth outcomes remained unchanged during the first COVID-19 lockdown in 2020 in most parts of Switzerland. The cause of the observed increased risk of preterm birth in Ticino needs to be followed up, as sample size was small and a chance finding cannot be ruled out.